Big Data and IoT for Chronic Patients Monitoring - Páez, Diego Gachet; Aparicio, Fernando; de Buenaga, Manuel; Ascanio, Juan R. (Ubiquitous Computing and Ambient Intelligence. Personalisation and User Adapted Services, 2014)
Recent data of the European Union reveals that the main chronic pathologies are the Cardiovascular Disease (CVD), the main cause of death in Europe, and respiratory diseases, specially the Chronic Obstructive Pulmonary Disease (COPD). Each year CVD causes over 4 million deaths in Europe alone and over 1.9 million deaths in the European Union (EU). According to the WHO (World Health Organization), in 2030 COPD will be the third leading cause of death, and the first cause of sanitary costs in Europe, due to the profiles of the expenses in health sector and the long time expenses by age groups and their important associate morbidity. New medical applications based on remote monitoring can help treat those chronic diseases but significantly will increase the volume of health information to manage, including data from medical and biological sensors, being then necessary to process this huge volume of data using techniques from Big Data. In this paper we propose one potential solution for creating those new services, based on Big Data processing and IoT concepts.